Cause, Setting and Ownership Analysis of Dog Bites in Bay County, Florida from 2009 to 2010. (9th April 2014) - Matthias, J.; Templin, M.; Jordan, M. M.; Stanek, D.
Summary Emergency room and hospital discharge data have been used to describe the risk factors and public health impact of dog bites. These data sets are based on financial charges for severe bites and underestimates dog bite burdens within communities. This study expands both the source of information and risk factor data collected to provide demographic analysis of dog bite injury risk factors reported in Bay County, Florida in 2009–2010. Extended data for dog bites reported by various sources from January 1, 2009 to December 31, 2010 were collected by Florida Department of Health in Bay County. Data collected included bite victim's age and gender, primary reported cause of bite, setting, dog's restraint status and relationship between the victim and the dog. A total of 799 bites were reported. Most bites (55%) were reported first by healthcare practitioners, particularly bites involving children <6 years. Bites involving unfamiliar dogs and dogs off the owner's property were more likely to be reported by other sources. Boys aged 6–14 years accounted for 2.24 times more bites than same‐aged females (P < 0.001) and had the highest incidence with 424 bites per 100 000 persons per year. Persons 6 years or older were 3.6 times more likely to be bitten by an unfamiliar dog. Inappropriate behaviour management was the most common cause of bites (26%), followed by protective behaviour (24%). Bites of unknown cause were 2.5 times more likely in children <6 years. Separating dog fights was the most common cause of bites for persons 15 years or older (24%); females were significantly more likely to be bit than males (P = 0.01). Bites by unrestrained dogs off the owner's property (32% of all bites) most commonly involved males. Estimates based solely on healthcare discharge data significantly underestimate dog bite burden within a community. Characterizing these risks by age group or gender provides an opportunity to implement targeted interventions to prevent dog bites.